2018
DOI: 10.29322/ijsrp.8.4.2018.p7653
|View full text |Cite
|
Sign up to set email alerts
|

Participation of Smallholder Vegetable Growers in High-Value Market Chains in Arusha, Tanzania

Abstract: Despite the huge employment and income benefits from vegetable farming, smallholder growers in developing countries lack the knowledge about high value markets and their requirements. Most of these growers are ignorant have limited knowledge about vegetable contract farming, product standardization and grading of their produce, quality of produce preferred by customers, on delivery times and food safety standards. This study used primary data collected from 200 smallholder vegetable growers in Arumeru District… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 2 publications
4
7
0
Order By: Relevance
“…This finding is in line with the findings of Muthini et al. (2017) and Sumari et al. (2018) who found that wealthier mango farmers and vegetable farmers, respectively, were more likely to participate in high value markets.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This finding is in line with the findings of Muthini et al. (2017) and Sumari et al. (2018) who found that wealthier mango farmers and vegetable farmers, respectively, were more likely to participate in high value markets.…”
Section: Discussionsupporting
confidence: 92%
“…High value markets, especially the export markets, require farmers to use approved farm inputs which are expensive but could be relatively affordable to wealthy farmers. This finding is in line with the findings of Muthini et al (2017) and Sumari et al (2018) who found that wealthier mango farmers and vegetable farmers, respectively, were more likely to participate in high value markets. Muthini et al (2017) argue that wealthy farmers can incur transaction and transportation costs associated with participating in remunerative markets.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations